Preferensi Generasi Milenial Untuk Berinvestasi Sukuk - Yanuar Pribadi (I-Finance Journal, 2020)
The study aims to analyze the preferences of millennials to invest in Sukuk instrument seen from investment risk factors (default risk, rate of return, liquidity), and sharia factors (financial activities according to sharia and avoiding ‘riba). Around 64 million Indonesian millennials are potential market for Sukuk market in the country. The research population were millennials who join the webinar of sukuk education for the millennial generation. Using the multiple linear regression analysis, the results indicated that risk factors and sharia factors had a positive effect both simultaneously and partially on the millennials preferences in Sukuk investments.